Logopeda wobec konsekwencji kolczykowania narządów zespołu ustno-twarzowego - Jachimowska, Katarzyna; Korycka, Agata (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
Piercing of different parts of human body is a phenomenon that can be met in medical practices of doctors of almost all specialties. Piercing cannot be considered harmless and people with oral piercing are a risk group of nourishment and respiratory activities disorders and articulation deterioration. Research results presented in the article prove the existence of “piercing dyslalia”. As a result of gathered material analysis it was also noted that orofacial group disorder can lead into new movements of compensatory character, including parafunctions. Oral piercing can cause abnormal habits of breathing and eating, which are important for the quality of articulation.